Globalization, Islam Nusantara, and contemporary character empowerment - Hirshi Anadza; Rommel Utungga Pasopati (Journal of Social, Humanity, and Education, 2021)
Purpose: The purpose of this research is to analyze how Islam Nusantara may contribute to contemporary character empowerment in today’s globalization era. Research methodology: This research uses textual studies in order to assert the interaction between Islam Nusantara and contemporary character empowerment. Results: The results of this study assess local values as reflected in Islam Nusantara could enrich human and cultural tolerance as the main ideas of character empowerment. Limitations: This study explains how globalization, Islam Nusantara, and contemporary character empowerment may work together today in Indonesia. Any other aspect such as different times, places, and themes should not be concerned. Contribution: Analyses in this study may enrich social and humanitarian understanding about local Islamic culture in Indonesia, horizons of globalization, and perspectives of contemporary character empowerment. Keywords: Character empowerment, Globalization, Industrial revolution 4.0, Islam Nusantara, Technological advancement